Analysis of English Learning Process in Man PK Man 2 Mataram - Nur Alfilail; Lela Rahmawati; Bidari Andaru Widhi; Hilmiyatun Hilmiyatun (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Learning process is crucial part in the process of teaching and learn English. Thus, this aspect is one of aspect where the teacher put the attention on especially for students in senior boarding school level. Since this aspect is essential, this present study aims at identifying English learning process in Man PK Man 2 Mataram as this school has several main purposes one of which is to strengthen students’ ability in using foreign language such as English. This study belongs to qualitative study were observation and interview became the technique of data collection. The result of study showed that there are several English learning activities that support the mastery of English skill including speaking and writing.